Benign Methodology and Efficient Catalysis for the One-Pot Multicomponent Synthesis of Dihydropyrimidinones and Thiones: A New Key for Old Lock. (9th April 2014) - Ali, Parvez; Pathan, Naziyanaz; Ben Hadda, Taibi
Abstract : In the present communication, under the influence of microwaves, cuprous chloride has been demonstrated to be safe, mild, efficient, and inexpensive catalyst for the Biginelli discovered multicomponent reaction (MCR) between aromatic aldehydes, urea/substituted urea, and ethyl acetoacetate to produce structurally diverse dihydropyrimidin-2(1H)-ones (DHPMs) and thiones in an ecofriendly solvent-free protocol. The practical and simple protocol led to excellent yields of the dihydropyrimidin-2(1H)-one derivatives under mild reaction conditions and within short span of reaction times with easy reaction workup by maintaining excellent atom economy.